Perceived Quality of Open and Distance Learning Resources and Effective Learner Support Services among Dual-mode Universities in Ghana - Abdulai, Munkaila; Awaah, Fred; Osei, Michael; Yayviah, Ernest (West African Journal of Open and Flexible Learning, 2022)
Open and Distance Learning (ODL) is a new phenomenon that is being steadily embraced in higher education space in Africa, particularly in Ghana. It is an innovation to the traditional bricks and mortar learning system in institutions of higher education and, if such novelty is not carefully managed and deployed, its essence may be misplaced. Administrators, instructors and learners are important collaborators in this project. Unfortunately, those collaborators are also new to ODL operations and their learning management systems. A major concern for learners remains effective learner support services while empowerment, skills development and infrastructure for teaching and learning are important for administrators and instructors. The paper explored the perceived quality of ODL resources and learner support services across Ghanaian ODL universities from students’ perspective. For this study, a sample of 503 respondents were randomly selected from five (5) ODL universities and quantitatively analyzed. The results revealed that instructors’ support was found to be unsatisfactory whilst the atmosphere of the learning center is considered non-conductive. Distance learning universities are recommended to invest more in technology-driven services that would enhance quality systems, and instructors support while attending to the needs of the learners quickly.